Risk factors for the prognostic effects of patients with pelvic abscesses: a clinical retrospective study - Lei Yang; Juhua Zhong; Huihua Chen; Chen Gao; Tingting Lin; Liangyu Chen; Zhenwen Zhang; Yang Lin; Yiyi Zheng (BMC Women's Health)
Abstract Background Pelvic abscesses represent acute gynecological emergencies requiring timely intervention. This study evaluated prognostic predictors and treatment modalities in patients with pelvic abscesses. Methods We conducted a retrospective analysis of 127 consecutive pelvic abscess cases treated at Ningde Municipal Hospital between 2016 and 2021. Patients were stratified by treatment modality (non-surgical, laparoscopic, open surgery). Multiple linear regression analyses were performed to assess the associations between risk factors and prognostic outcomes. Results Non-surgical management was associated with smaller abscess size but longer recovery times compared to surgical interventions. Laparoscopic approaches exhibited superior outcomes versus open surgery in both operative time and blood loss. Multivariate analysis identified key prognostic factors included treatment modality, duration from onset to admission, pre-admission temperature, CA125 levels, and maximum mass diameter. Conclusions These findings underscore the prognostic value of early intervention, biomarker-guided decision-making, and minimally invasive approaches in pelvic abscess management. By identifying these factors, healthcare providers could effectively stratify patients based on their risk profiles, facilitating more personalized treatment strategies and improved prognostic outcomes.